Bibliometric analysis of scientific literature on the use of suppositories in the treatment of prostate cancer patients - I. V. Bushuieva; M. V. Parchenko; O. O. Maliuhina (Aktualʹnì Pitannâ Farmacevtičnoï ì Medičnoï Nauki ta Praktiki, 2024)
Nowadays, cancer remains one of the main causes of death worldwide. Statistical data from various literary sources indicate that more than 130,000 people in Ukraine receive this diagnosis as a sentence every year. Cancer can affect any organs of the human body and, over time, the entire organism. In 2024, the agency of the World Health Organization on cancer and the International Agency of Cancer Research published the latest statistical estimates of this pathology in a global format, where prostate cancer is among the five most common oncological pathologies and takes the fourth place. Oncological diseases are one of the priority areas of healthcare development in accordance with the Order of the Ministry of Health of Ukraine No. 1832 dated 07.10.2022 “On Approval of Priority Areas of Healthcare Development for 2023–2025”. It was this fact that determined the choice of the direction of this research in the matter of finding information on the provision of pharmaceutical care, namely the use of a drug – a rectal suppository for the treatment of prostate cancer.